2001
DOI: 10.1016/s0092-8674(01)00229-x
|View full text |Cite
|
Sign up to set email alerts
|

SNARE Complex Oligomerization by Synaphin/Complexin Is Essential for Synaptic Vesicle Exocytosis

Abstract: Synaphin/complexin is a cytosolic protein that preferentially binds to syntaxin within the SNARE complex. We find that synaphin promotes SNAREs to form precomplexes that oligomerize into higher order structures. A peptide from the central, syntaxin binding domain of synaphin competitively inhibits these two proteins from interacting and prevents SNARE complexes from oligomerizing. Injection of this peptide into squid giant presynaptic terminals inhibited neurotransmitter release at a late prefusion step of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(139 citation statements)
references
References 59 publications
4
134
1
Order By: Relevance
“…Munc18a and Munc13-1 have been shown to be "priming" factors that increase the release potential for a given population of vesicles (Ashery et al, 2000;Voets et al, 2001). Complexins are also purported to play a role in SNARE complex assembly and stabilization (Reim et al, 2001;Tokumaru et al, 2001). Though a dysfunction in any of these proteins could lead to an increase in SNARE complexes, no alterations in their levels were detected in the amygdalar kindled animals (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Munc18a and Munc13-1 have been shown to be "priming" factors that increase the release potential for a given population of vesicles (Ashery et al, 2000;Voets et al, 2001). Complexins are also purported to play a role in SNARE complex assembly and stabilization (Reim et al, 2001;Tokumaru et al, 2001). Though a dysfunction in any of these proteins could lead to an increase in SNARE complexes, no alterations in their levels were detected in the amygdalar kindled animals (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The five bands representing 7S SNARE complexes (bands indicated in Fig. 1A) may be SNARE oligomers, as suggested by (Tokumaru et al, 2001). These bands were quantified and their sum was considered the total 7S SNARE complex in that synaptosomal preparation.…”
Section: Kindling Increases 7s Snare Complexes In Hippocampal Synaptomentioning
confidence: 99%
See 1 more Smart Citation
“…To establish whether binding partners of complexins were present (Tokumaru et al, 2001), the distribution of syntaxin-1 was determined in rabbit retina. Syntaxin-1 immunoreactivity was robust in the IPL and outlined numerous amacrine cell bodies in the proximal INL (Fig.…”
Section: Syntaxin-1mentioning
confidence: 99%
“…Initial studies suggested that multimerization of synaptic SNARE complexes could be achieved via domain swapping, whereby one of the two SNAP-25 helices could be substituted by the equivalent helix from a neighboring complex (Kweon et al, 2002). Alternative models proposed the involvement of accessory proteins, such as synaptotagmin (Littleton et al, 2001) or complexin (Tokumaru et al, 2001), or the transmembrane domains of syb2 and syntaxin 1A (Laage et al, 2000), in synaptic SNARE complex multimerization. However, SNARE complexes assembled from recombinant coils and lacking transmembrane domains are able to associate with each other (Fasshauer et al, 1997;Fasshauer et al, 1998;Margittai et al, 2001;Ernst and Brü nger, 2003), arguing that at least some of the interactions that support multimerization may require neither accessory proteins nor transmembrane domains.…”
Section: Introductionmentioning
confidence: 99%